2018
DOI: 10.1002/jcb.27260
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of mesenchymal stem cell–derived exosomes on experimental type‐1 autoimmune diabetes

Abstract: Exosomes derived from adipose tissue-derived mesenchymal stem cells (AD-MSCs) have immunomodulatory effects of T-cell inflammatory response and reduction of clinical symptoms on streptozotocin-induced of the type-1 diabetes mellitus (T1DM). Beside control group and untreated T1DM mice, a group of T1DM mice was treated with intraperitoneal injections of characterized exosomes derived from autologous AD-MSCs. Body weight and blood glucose levels were measured during the procedure. Histopathology and immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 47 publications
2
152
0
1
Order By: Relevance
“…However, other studies have reported that SC-EVs inhibited the proliferation of NK cells and B cells, although its effect on the proliferation of T cells remains unclear (30,108). There are evidences that indicate that SC-EVs do not suppress T cell proliferation; however, they induce upregulation of Tregs and downregulation of pro-inflammatory cytokines (51,74,109).…”
Section: T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies have reported that SC-EVs inhibited the proliferation of NK cells and B cells, although its effect on the proliferation of T cells remains unclear (30,108). There are evidences that indicate that SC-EVs do not suppress T cell proliferation; however, they induce upregulation of Tregs and downregulation of pro-inflammatory cytokines (51,74,109).…”
Section: T Cellsmentioning
confidence: 99%
“…On the one hand, SC-EVs have been reported to induce the immune response of T helper type 1 (Th1) conversion to T helper type 2 (Th2). For example, SC-EVs drove the shift from Th1 toward Th2 cells and reestablished Th1/Th2 homeostasis by downregulating pro-inflammatory TNF-α and INF-γ and upregulating anti-inflammatory IL-10 or IL-4 (29,44,51,74,76) ( Table 1). Moreover, SC-EVs could also regulate Th2 immune response toward Th1.…”
Section: Stem Cell-derived Extracellular Vesicle Potentials In T Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using PBMC cells from type I diabetes patients, MSC-EV administration decreased Th17 response while increased Treg response [65]. Based on that, we differentiated lymphocytes to a pro-inflammatory condition (Th1) and as it was shown previously with MSCs treatment [66,67], a significant reduction of IFN-γ-secreting cells was observed after treatment with MSC-EVs. We then differentiated to another pro-inflammatory condition, Th17, but we did not see effect on T cell differentiation.…”
Section: Discussionmentioning
confidence: 69%
“…Exosomes isolated from MSCs can also be used in the treatment of T1D, as they are immunomodulatory and favour cell survival. Hence, treatment with hucMSCs exosomes improved pancreatic function in STZ‐treated mice by increasing the population of regulatory T cells and their anti‐inflammatory products IL‐4 and IL‐10 …”
Section: Exosomes As Therapy For Diabetesmentioning
confidence: 99%